THE USE OF DIFFERENT ACID SOLVENTS IN MINERAL EXTRACTION OF SEA CUCUMBER (Holothuria atra) - Intan Elisa; Suardi Loekman; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was aimed to determine of chemical compositions, yield, the best of acid solvent extraction, and mineral content of skin meat of sea cucumber (Holothuria atra). The method used in this study was an experimental method which extracting of skin meat of sea cucumber with 8% concentrations of different acid solvents using non-factorial Completely Randomized Design (CRD) consisting of 3 treatment levels: HCl (P1), HNO3 (P2), and H2SO4 (P3). The parameters tested in this study were moisture, protein, fat, ash, carbohydrate, yield and mineral content of calcium, potassium, sodium, and iron using the Atomic Absorption Spectrophotometer (AAS). The results showed that the chemical compositions of skin meat of sea cucumber were  10.05% (WW) moisture, 53.16% protein (DW), 3.64% fat (DW), 32.85% (DW) ash, carbohydrate content 10.35% (DW) by difference, and the yield of flour in skin meat sea cucumber was 20.79%. The use of different acid solvents have a very significant affect on mineral content, wherein the best acid solvent was HCl (P1) which contained 7.53% calcium, 2.87% potassium, 0.93% sodium, and 1.79% iron. Keywords: Mineral, Holothuria atra, acid, solvent